Exogenous Spermidine Priming Mitigates the Osmotic Damage in Germinating Seeds of Leymus chinensis Under Salt-Alkali Stress - Hongna, Chen; Junmei, Shi; Leyuan, Tao; Xiaori, Han; Guolin, Lin; Xianguo, Cheng (Frontiers in Plant Science, 2021)
Abstract: Spermidine usually functions in protecting macromolecules involved in the biochemical-physiological processes in plants. For exploring whether spermidine participates in the responsive regulation of the seed germination of Leymus chinensis to salt-alkali stress, we used spermidine as priming agent to soak the seeds of Leymus chinensis before sowing, and performed a culture experiment of soils with salinization-alkalinization. Physiological measurements showed that spermidine priming significantly increased the accumulation of proline and soluble sugar, thus protecting the antioxidant enzyme system, and lowering the damage of reactive oxygen species to the plasma membrane in the germinating seeds. Exogenous spermidine promoted the reverse synthesis of polyamines in the germinating seeds, thus enhancing the activity of polyamine oxidase and triggering the proper accumulation of hydrogen peroxide in the germinating seeds. Hydrogen peroxide further modulated cytosolic calcium ion level, and beneficially changed the accumulation profiles of hormones in the germinating seeds, thus breaking the dormancy-inducing pathways of the germinating seeds of Leymus chinensis, and further improving the vitality and germination rate of Leymus chinensis seeds in response to salt-alkali stress. This study showed that exogenous spermidine priming could effectively mitigate the osmotic damage of salt-alkali stress in the germinating seeds of Leymus chinensis.